THE STUDY OF HOLISTIC MISSION SERVICES FROM A CHRISTIAN PERSPECTIVE - Suwito, Tri Prapto; Rusmanto, Andreas (IJOSMAS, 2022)
This study was carried out with the aim of providing a fresh understanding to the church and Christianity about holistic mission, specifically referring to the description pericope Luke 9:1-6. Jesus sent the twelve disciples. It is also to refresh the purpose of the holistic mission. The researcher found several things about holistic mission as the core of this study. There is a holistic mission that is carried out through a mission, carried out by the apostles followed by the Church, a holistic mission that requires transformation or change, then a holistic mission that proclaims about the Kingdom of God.